Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijerph17010119
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Living Status Transitions, Behavior Changes and Family Relationship Improvement among Methadone Maintenance Treatment Participants in Guangdong, China

Abstract: The quality of family relationships is important for individual and family well-being. Improving family relationships is also an important goal in methadone maintenance treatment (MMT). Little is known about factors associated with the improvement of family relationships among MMT clients. This study aimed to identify factors associated with family relationship improvement in MMT. We retrospectively analyzed existing data from 2006 to 2014 at 15 MMT clinics in Guangdong, China, including 2171 subjects with 469… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, as a vulnerable group for mental health issues, they experienced a decrease in negative emotions and an increase in self-confidence after being treated. Better health status facilitated their reintegration into society [ 25 ], leading to closer family relationships and more employment opportunities. According to Sun et al [ 26 ], the overall employment rate of MMT participants increased from 26.4% at baseline to 41.6% after 6-month treatment and to 59.8% after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as a vulnerable group for mental health issues, they experienced a decrease in negative emotions and an increase in self-confidence after being treated. Better health status facilitated their reintegration into society [ 25 ], leading to closer family relationships and more employment opportunities. According to Sun et al [ 26 ], the overall employment rate of MMT participants increased from 26.4% at baseline to 41.6% after 6-month treatment and to 59.8% after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The discriminative role of living conditions, in our study social and isolation housing, is consistent with the literature pointing out the quality of living environment as a critical intervening factor determining treatment efficacy in neuropsychiatric diseases, such as depression (see review (Branchi and Giuliani 2021 )). Although a role of living conditions in the vulnerability to addiction has been shown (Ajonijebu et al 2017 ; Caprioli et al 2007 ), little is known about their impact on the therapeutic efficacy to prevent relapse (Liu et al 2019 ; Polcin et al 2010 ). In this study, we demonstrated that a social living environment favours a positive interaction (synergism or additive effect) between EE and fluoxetine in inhibiting sucrose relapse in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…A critical factor determining the therapeutic efficacy, especially of pharmacological treatments, is the living environment (i.e., family, home, work and social environments). The relevant role of living environment on treatment outcome has been extensively demonstrated for depression (see review (Branchi and Giuliani 2021 )) and, recently, in a few studies on addiction (Liu et al 2019 ; Polcin et al 2010 ; Solinas et al 2010 ). Clinical and preclinical evidence showed that SSRIs antidepressant efficacy is positively modulated by the quality of the living environment (low vs. high social economic status in humans, stressed vs. enriched condition in mice) (Branchi et al 2013 ; Chiarotti et al 2017 ; Viglione et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%